Solid effervescent composition

By using inorganic binders, gas generators, strong and weak acid cleaning compositions, the problem of using irritating chemicals in existing cleaning toilet products is solved, and effective cleaning and environmentally friendly effects are achieved for flush toilets.

CN119421942APending Publication Date: 2025-02-113M INNOVATIVE PROPERTIES CO
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380049492.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-06-14
Filing Date
2023-06-28
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

Most of the existing toilet cleaning products contain bleach or other irritating chemicals, which lead to unpleasant odors and environmental problems, and are unable to thoroughly clean the toilet.

Method used

The cleaning compositions containing inorganic binders, gas generators, strong and weak acids are employed, which produce effervescent, foaming and acidic after dissolving in water, have good stability, and can be combined with other materials to prepare each Cleaning products.

Benefits of technology

It realizes the effective cleaning of the flush toilet without using irritating chemicals, and is environmentally friendly, with few residues, oxidation and effervescent capabilities, and can provide a protective layer for easier cleaning.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005205997790000111
    Figure BDA0005205997790000111
  • Figure BDA0005205997790000131
    Figure BDA0005205997790000131
  • Figure BDA0005205997790000132
    Figure BDA0005205997790000132
Patent Text Reader

Abstract

In one embodiment, the present invention is a cleaning article comprising: an inorganic binder; a gas generating agent; a strong acid having a pKa of between about-3 and about 2; a weak acid having a pKa of between about 2.5 and about 5 wherein the ratio of strong acid to weak acid is between about 50: 1 and about 1: 50; and at least about 0.1% water. When the cleaning article has a diameter of about 48 mm and a height of about 21 mm and a recess diameter of about 29.8 mm, a recess height of about 12.8 mm, and a mass of about 40 g, the cleaning article has a tablet breaking force of at least about 10 lbf and a dissolution time of between about 1 minute and about 60 minutes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention generally relates to the field of cleaning compositions. In particular, the present invention is a cleaning composition for toilets. Background Art

[0002] Cleaning a toilet is an unwelcome yet necessary task. Current methods of cleaning a toilet typically involve applying a cleaning agent to the inside of the toilet bowl and then scrubbing the bowl with a handheld tool. The handheld tool typically includes bristles or a cleaning head that can be used to flush the inside surface of the toilet bowl, removing debris and stains. The need to manually scrub the toilet bowl requires the person cleaning the toilet to be very close to the toilet, a situation that most people find unpleasant.

[0003] In an effort to keep more distance from the toilet bowl while cleaning it, various products have been developed that can be dropped into the toilet bowl to clean debris and stains without having to manually scrub the toilet bowl. However, most of these products include bleach or other harsh chemicals that have unpleasant, pungent odors and problematic environmental characteristics that can kill microbial soils. Other products do not contain bleach, but do not thoroughly clean the toilet bowl. Summary of the invention

[0004] In one embodiment, the present invention is a cleaning article comprising: an inorganic binder; a gas generating agent; a strong acid having a pKa between about -3 and about 2; a weak acid having a pKa between about 2.5 and about 5, wherein the ratio of strong acid to weak acid is between about 50:1 and about 1:50; and at least about 0.1% water. When the cleaning article has a diameter of about 48 mm and a height of about 21 mm and a depression diameter of about 29.8 mm, a depression height of about 12.8 mm, and a mass of about 40 grams, the cleaning article has a tablet breaking force of at least about 10 lbf and a dissolution time of between about 1 minute and about 60 minutes.

[0005] In another embodiment, the present invention is a solid cleaning composition comprising: an inorganic binder that reacts with water to harden to form a hardened structure; a gas generator; a strong acid having a pKa between about -3 and about 2; and a weak acid having a pKa between about 2.5 and about 5, wherein the strong acid and the weak acid are present in a ratio between about 50:1 and about 1:50; and an aqueous polymer. DETAILED DESCRIPTION

[0006] The present invention is a composition that can be used to make compressed cleaning products. After the composition is dissolved in water, it produces effervescence, foaming and acidity. In addition, the composition can be pressed into solid products at room temperature and low temperature. The composition has good stability at room temperature and high temperature. In one embodiment, the composition can be used with other materials such as surfactants, fragrances, abrasives, minerals, biocides, antimicrobial agents and colorants to allow the production of a variety of cleaning products. In addition, the composition of the present invention is environmentally friendly and is benign to humans and the environment. The composition can be completely dissolved in water, and there is very little residue after cleaning. The key characteristics of this composition can be adjusted according to the needs of product development to particularly enhance oxidation capacity, acidity or effervescence. In addition, the composition of the present invention also provides a protective layer on the surface to be cleaned, thereby allowing the surface to be cleaned more easily later. The composition can be molded into a cleaning product under pressure at room temperature. The cleaning product can gradually dissolve in the presence of water, producing effervescence, foaming, acidity and abrasive properties, thereby achieving effective cleaning. In one embodiment, the composition is used to clean and / or remove stains, such as hard water stains from toilets.

[0007] Said composition generally comprises inorganic binder, organic binder, gas generant, strong acid, weak acid and aqueous liquid.In one embodiment, said composition comprises inorganic binder between about 0.1 wt % and about 30 wt %, organic binder between about 0.1 wt % and about 30 wt %, gas generant between about 5 wt % and about 60 wt %, strong acid between about 1 wt % and about 70 wt %, weak acid between about 1 wt % and about 70 wt % and aqueous liquid between about 0.1 wt % and about 20 wt %.Especially, said composition comprises inorganic binder between about 1 wt % and about 5 wt %, organic binder between about 1 wt % and about 20 wt %, gas generant between about 10 wt % and about 40 wt %, strong acid between about 5 wt % and about 60 wt %, weak acid between about 5 wt % and about 60 wt % and aqueous liquid between about 1 wt % and about 10 wt %.

[0008] Inorganic and organic binders serve to hold the components of the composition together. The binder must be strong enough to maintain mechanical integrity and provide hardness to the composition until the composition comes into contact with water, at which point it can dissolve. In the presence of an aqueous liquid, the binder can chemically or physically hold the components of the composition together, forming covalent bonds, ionic bonds, hydrogen bonds, van der Waals interactions or other secondary interactions. The binder can be chemically reactive or non-chemically reactive during the bonding process.

[0009] Inorganic binders react with water to cause the composition to harden. Hardening refers to the reaction of inorganic binders with water to form a new hydrated form, or the condensation and crosslinking of inorganic binders in the presence of water. The hardened inorganic binder provides structural support for the composition and resists degradation caused by water. During the hardening process, the inorganic binder can form hydrogen bonds with other components, thereby improving the structural integrity of the composition. Compared with non-reactive binders, the use of inorganic binders that react with water can significantly improve the hardness and mechanical integrity of the composition after the composition is compressed under the same force at room temperature. After forming a compressed product, the composition containing a reactive inorganic binder can maintain sufficient hardness, mechanical integrity and durability for scrubbing and cleaning, while, for example, when in contact with water in a toilet bowl, the swelling of the formed geometry is minimal. When used in water or in a humid environment, it is the strong bonding ability of the reactive inorganic binder that makes the compressed product durable. The durability of the compressed article in the wet state can be quantified by the number of cycles that the compressed article can be moved back and forth linearly at a selected path length (5 cm, 10 cm, 20 cm) and speed; or in the wet state, under a certain applied weight (0.5 kg, 1.0 kg, 2.0 kg, 5 kg, 10 kg) on ​​a suitable machine (e.g., Taber Linear Abrasion Tester or Taber Rotating Platform Abrasion Tester, North Tonawanda, NY) by the selected number of cycles on a circular path and speed. The wet state refers to the state in which the compressed article is immersed in water and then removed during the test, or immersed in water. In order to simulate the use of the compressed article in water or in a wet environment, the compressed article having a cylindrical geometry (4 cm in diameter and 0.25 cm, 0.38 cm, 0.50 cm, or 0.56 cm in height) is first immersed in water to allow the water to fully penetrate the compressed article, pressed on a hard surface, and then moved back and forth by hand for a path length of about 20 cm. When used in a wet state, the compressed article is considered to exhibit sufficient "wet hardness", i.e., sufficient mechanical integrity and durability. When rubbed against a hard surface with force applied by hand, the compressed article effervesces and foams, and gradually loses mass during simulated cleaning.

[0010] When used in water, the compressed product containing non-reactive binder will lose its hardness and mechanical integrity or swelling in a short period of time (e.g., less than about 2 minutes, and particularly about 30 seconds, depending on the size of the product). The hardness of the composition can be measured, for example, by compressing the durometer of Shore A or D on the surface of the composition according to the procedure described in ASTM D 2240-00. The aging hardness is the hardness measured on the compressed composition aged for two weeks in air at room temperature. The example of particularly suitable reactive inorganic binder includes, but is not limited to, calcium sulfate hemihydrate, calcium sulfate anhydrous, sodium silicate, sodium metasilicate, potassium silicate, potassium metasilicate, lithium metasilicate, lithium silicate, cement and combinations thereof. The example of particularly suitable reactive inorganic binder includes, but is not limited to, a binder composition based on the formulation of calcium sulfate hemihydrate, such as DURABOND 20, DURABOND 45 and DURABOND 90 purchased from USG (USG, located in Chicago, IL) located in Chicago, Illinois.

[0011] Water or aqueous liquid is used as a reactant with the inorganic binder, as a medium for the reaction of other components in the composition, and as a carrier for additives. The reactive inorganic binder can react with the water in the aqueous liquid to harden and provide hardness and mechanical integrity to the composition. The water in the aqueous liquid can also serve as a medium for the reaction of the acid and the gas generating agent and generate more water, which produces hydrogen bonding in the composition to improve hardness and mechanical integrity. The aqueous liquid has a water content sufficient to react with the binder. In one embodiment, the aqueous polymer is a hydrophilic polymer that not only provides water to interact with the inorganic binder, but also leaves a hydrophilic polymer film on the surface to make it easier to clean after the compressed composition is dissolved. In one embodiment, the aqueous liquid has a water content of at least about 0.1%, particularly at least about 1% by weight. Examples of suitable aqueous liquids include, but are not limited to: water, aqueous solutions of inorganic compounds, aqueous solutions of polymers, aqueous dispersions of polymers, aqueous dispersions of organic molecules, liquid organic compounds, mixtures of liquid water and organic compounds, aqueous solutions of organic compounds, and combinations thereof. Examples of suitable liquids include, but are not limited to, deionized water, calcium chloride aqueous solution, calcium acetate aqueous solution, sodium acetate aqueous solution, polyacrylic acid and its sodium salt aqueous solution, polyvinyl alcohol aqueous solution, polyvinyl pyrrolidone aqueous solution, polyethylene glycol aqueous solution, polyethylene imine aqueous solution, polystyrene sulfonate aqueous solution, polyester aqueous solution, polyurethane aqueous dispersion, polyvinyl acetate aqueous dispersion, styrene butadiene rubber aqueous dispersion, polyacrylate aqueous dispersion, polyamide aqueous dispersion, polyolefin aqueous dispersion, polyacrylic acid acrylamide aqueous dispersion, other hydrophilic polymer aqueous dispersion, rosin and its derivative aqueous dispersion, mixture of water and acetic acid, mixture of water and lactic acid, glycolic acid aqueous solution, and gluconic acid aqueous solution, fragrance aqueous dispersion, pigment aqueous dispersion, dye aqueous solution, and combinations thereof. Examples of commercially suitable aqueous liquids include, but are not limited to, Mirapol Surf-S110, 500 and 900, available from Solvay, Brussels, Belgium; Sorez TM 100, HS205, purchased from Ashland, Wilmington, DE, USA; Noverite TM K-732, K-739, available from Lubrizol, Brecksville, OH, USA; and Sokalan, available from BASF, Ludwigshafen, Germany.

[0012] Gas generators are used as effervescent agents to generate foam / bubbles. By generating foam and / or bubbles, the composition is able to reach additional surface area. Gas generators are essential components that interact with the acid in the composition to provide effervescence. Examples of suitable gas generators include, but are not limited to, carbon dioxide generators and oxygen generators. Examples of suitable carbon dioxide generators include, but are not limited to, bicarbonates of Group I metals, Group II metals and other cations (including ammonium, alkyl (mono-, di- or tri-) ammonium), or transition metals; carbonates of Group I metals, Group II metals and other cations (including ammonium, alkyl (mono-, di- or tri-) ammonium), or transition metals; and percarbonates of Group I metals, Group II metals and other cations (including ammonium, alkyl (mono-, di- or tri-) ammonium), or transition metals. Examples of particularly suitable carbon dioxide generators include, but are not limited to, sodium carbonate, sodium bicarbonate, potassium carbonate, potassium bicarbonate and calcium bicarbonate.

[0013] In order to produce maximum foam in the effervescent system of the composition, the equivalent concentration ratio of the acid and the base in the composition should be about 1. The equivalent concentration ratio is defined as the equivalent molar number of the acidic functional groups in the formulation versus the equivalent molar number of the basic functional groups. When this ratio deviates from 1, the total amount of foam in the system will be reduced accordingly. In one embodiment, the ratio of the acid to the base of the composition is between about 10:1 and about 1:10, specifically between about 5:1 and about 1:5, and more specifically between about 3:1 and about 1:3.

[0014] Examples of suitable oxygen generators include, but are not limited to, hydrogen peroxide; peracetic acid produced from sodium percarbonate / TAED (tetraacetylethylenediamine); percarbonates of Group I metals, Group II metals and other cations (including ammonium, alkyl (mono-, di- or tri-) ammonium), or percarbonates of transition metals; chlorates and perchlorates of Group I metals, Group II metals and other cations (including ammonium, alkyl (mono-, di- or tri-) ammonium), or chlorates and perchlorates of transition metals; superoxide salts of Group I metals, Group II metals and other cations (including ammonium, alkyl (mono-, di- or tri-) ammonium), or superoxide salts of transition metals; and peroxide salts of Group I metals, Group II metals and other cations (including ammonium, alkyl (mono-, di- or tri-) ammonium), or peroxide salts of transition metals.

[0015] The acid acts as an effervescent agent and a cleaning agent. The composition comprises a strong acid and a weak acid. The strong acid and the weak acid must be present in a specific ratio in order to provide foaming and the desired dissolution time. In one embodiment, the weight ratio of the strong acid to the weak acid is between about 50:1 and about 1:50, and in particular between about 11:1 and about 1:11. In one embodiment, the normal ratio of the strong acid to the weak acid is between about 3:1 and about 1:3, and in particular about 1:1.

[0016] Strong acids are defined as acids with a pKa between about -3 and about 2. Strong acids serve to provide rapid foaming and are generally less hygroscopic. In one embodiment, the strong acid may also perform a disinfecting function. In one embodiment, the strong acid is one of an alkyl sulfonic acid, an aryl sulfonic acid, and an oxalic acid. Examples of suitable alkyl sulfonic acids and aryl sulfonic acids include, but are not limited to, aminosulfonic acid, p-toluenesulfonic acid, and methanesulfonic acid.

[0017] A weak acid is defined as an acid having a pKa between about 2.5 and about 5. Weak acids are generally more hygroscopic than strong acids and thus can provide strong bonding, thereby increasing tablet strength. Weak acids can also contribute to slow initial foaming, but the total foaming is higher. In one embodiment, the weak acid is a carboxylic acid. Examples of suitable weak acids include, but are not limited to, formic acid, acetic acid, propionic acid, butyric acid, lactic acid, sorbic acid, fumaric acid, malic acid, tartaric acid, citric acid, benzoic acid, adipic acid, ascorbic acid, and glycolic acid.

[0018] Other additives may be included in the composition to perform various functions. Examples include, but are not limited to, chelating agents, surfactants, oxidants, biocides, antimicrobial agents, anti-caking agents, hydrophilic agents, dispersants, co-binders, processing aids, fillers / tougheners, softeners, abrasive particles, desiccants, mold release agents, lubricants, disintegrants, detergents, coupling agents, photoinitiators, thermal initiators, viscosity modifiers, tackifiers, grinding aids, wetting agents, dispersants, light stabilizers, antioxidants, defoamers, colorants, dyes, pigments, and aromatics. Particularly suitable additives include components that help improve the stability of the composition before compression and forming compressed products. Examples include anti-caking agents, dispersants, and co-binders. Particularly suitable additives that help the demoulding of compressed products include, but are not limited to, mold release agents and lubricants.

[0019] The composition may also include an organic binder. In addition to the inorganic binder, an organic binder is added to the composition to improve overall tablet strength. In particular, the organic binder improves the impact strength of the final product, thereby increasing its durability. In addition, the organic binder helps the manufacturing process of the compressed cleaning product by preventing the brittleness of the composition.

[0020] Examples of suitable organic binders include, but are not limited to, sugars (such as glucose, fructose, galactose, sucrose, lactose, maltose, and liquid glucose), organic acid salts (such as sodium acetate, calcium acetate, sodium propionate, sodium glycolate, and sodium citrate), polymers (such as hydroxypropyl cellulose, methyl cellulose, ethyl cellulose, hydroxypropyl methyl cellulose, sodium carboxymethyl cellulose, gelatin, gum arabic, chitosan, alginic acid, starch, polyvinyl pyrrolidone, polyvinyl alcohol, polyethylene glycol, acrylate polymers, polyurethane, styrene-butadiene rubber, polyester, polyamide, polyethylene imine, vinyl polymers, and combinations thereof. Examples of particularly suitable organic binders include polyethylene glycol, particularly low molecular weight polyethylene glycol. Examples of particularly suitable polyethylene glycols include polyethylene glycols having an average molecular weight range of less than about 20,000 g / mol, specifically between about 400 g / mol and about 10,000 g / mol, and more specifically between about 4,000 g / mol and about 6,000 g / mol. The average molecular weight of the solid polyethylene glycol allows the polyethylene glycol to dissolve quickly in water. The cohesive strength of the polyethylene glycol within this average molecular weight range ensures that the compressed composition is not too hard, which would result in a longer dissolution time. As used herein, "molecular weight" refers to the weight average molecular weight measured using standard gel permeation chromatography methods known in the art.

[0021] When a processing aid is included for tablet or tablet manufacturing, it will reduce the stickiness of the tablet on the die surface, which will allow the tablet to be easily released from the punch holes of the die. The processing aid can be a stearate, such as magnesium stearate, mineral oil and silicate.

[0022] When a chelating agent is included in the composition, the chelating agent primarily acts as a complex forming agent with metal ions dissolved in water or deposited as stains on the toilet bowl surface. It also promotes cleaning as well as foaming. Examples of suitable chelating agents include, but are not limited to, citric acid and its sodium salt, ethylenediaminetetraacetic acid (EDTA) and its sodium salt, ethylene glycol tetraacetic acid (EGTA) and its sodium salt, and maleic acid and its sodium salt.

[0023] When a surfactant is included in the composition, the surfactant is used as a cleaning and foaming agent. Examples of suitable surfactants include, but are not limited to, anionic surfactants, nonionic surfactants, cationic surfactants, zwitterionic surfactants, amphoteric surfactants, oligomeric and polymeric surfactants. Examples of suitable anionic surfactants include, but are not limited to, alkyl and alkyl ether sulfates, sulfated monoglycerides, sulfonated olefins, alkyl aryl sulfonates, primary or secondary alkyl sulfonates, alkyl sulfosuccinates, acid taurates, alkyl sulfoacetates, acid isethionates, alkyl glyceryl ether sulfonates, sulfonated methyl esters, sulfonated fatty acids, alkyl phosphates, acyl glutamates, acyl sarcosinates, alkyl lactylates, anionic fluorosurfactants, sodium lauroyl glutamate, and combinations thereof. Other suitable anionic surfactants include those disclosed in U.S. Patent Application No. 61 / 120,765, and those disclosed in McCutcheon's Detergents and Emulsifiers, North American Edition (1992), Allured Publishing Corp. Examples of suitable nonionic surfactants include, but are not limited to, polyoxyethylated alkylphenols, polyoxyethylated alcohols, polyoxyethylated polyoxypropylene glycols, glycerol esters of alkanoic acids, polyglycerol esters of alkanoic acids, propylene glycol esters of alkanoic acids, sorbitol esters of alkanoic acids, polyoxyethylated sorbitol esters of alkanoic acids, polyoxyethylene glycol esters of alkanoic acids, polyoxyethylated alkanoic acids, alkanolamides, N-alkyl pyrrolidones, alkyl glycosides, alkyl polyglucosides, alkyl amine oxides, and polyoxyethylated siloxanes. Examples of suitable cationic surfactants include, but are not limited to, those selected from the class of "quaternary ammonium" materials, including, but not limited to, cetyltrimethylammonium chloride, behenyltrimethylammonium chloride, stearyltrimethylammonium chloride, cetylpyridinium chloride, octadecyltrimethylammonium chloride, cetyltrimethylammonium chloride, octyldimethylbenzylammonium chloride, decyldimethylbenzylammonium chloride, stearyldimethylbenzylammonium chloride, didodecyldimethylammonium chloride, distearyldimethylammonium chloride, tallowtrimethylammonium chloride, cocotrimonium chloride, dipalmitoylethyldimethylammonium chloride, PEG-2 oleyl ammonium chloride, and salts thereof, wherein the chlorine is replaced by a halogen (e.g., bromine), acetate, citrate, lactate, glycolate, phosphate nitrate, sulfate, or alkyl sulfate.Examples of suitable zwitterionic and amphoteric surfactants include, but are not limited to, amine oxides, betaines (carboxylic acid / quaternary ammonium or carboxylic acid / phosphonium), sulfobetaines or carboxybetaines, sultaines (sulfonic acid / quaternary ammonium or sulfonic acid / phosphonium), amino acid derivatives, imidazoline derivatives, lecithin and phospholipids. Examples of suitable polymeric surfactants include, but are not limited to, block copolymers of ethylene oxide and fatty alkyl residues, block copolymers of ethylene oxide and propylene oxide, hydrophobically modified polyacrylates, hydrophobically modified celluloses, silicone polyethers, silicone copolyol esters, polydimethylsiloxane diquaternary ammonium salts and co-modified amino / polyether silicones.

[0024] When the composition includes an oxidant, the oxidant serves to oxidize organic stains and remove bacteria. Examples of suitable oxidants include, but are not limited to, sodium persulfate, potassium persulfate, ammonium persulfate, sodium percarbonate, urea peroxide, a complex of polyvinylpyrrolidone and hydrogen peroxide, sodium perborate, peracetic acid, and combinations thereof. Examples of suitable commercially available oxidants include, but are not limited to, Oxone, available from Dupont, Wilmington, Delaware. In one embodiment, when the solid composition includes an oxidant, the solid composition includes up to about 15% by weight of the oxidant, particularly up to about 5% by weight of the oxidant.

[0025] The composition may include an anti-caking agent to contribute to the stability of the final product. In one embodiment, the anti-caking agent is hydrophobic. Examples of suitable anti-caking agents include, but are not limited to, fumed silica, fumed alumina, clay, and corn starch. In one embodiment, when the solid composition includes an oxidant, the solid composition includes up to about 15% by weight of the anti-caking agent, particularly up to about 5% by weight of the anti-caking agent.

[0026] The composition may optionally contain a biocide to remove bacteria. Examples of suitable biocides include, but are not limited to, benzalkonium chloride, sodium dichloroisocyanurate, benzisothiazolinone chlorhexidine, chlorhexidine, quaternary ammonium derivatives, and combinations thereof. In one embodiment, when the composition contains a biocide, the solid composition contains up to about 5% by weight of the biocide, particularly up to about 2% by weight of the biocide.

[0027] The composition has an acidic pH, making it useful for cleaning surfaces etched by protons in aqueous solution, such as toilet bowls. In addition, hard water stains and scale can be dissolved under acidic conditions. Alkaline pH is conducive to the formation of hard water stains and deposits of organic matter on toilet bowls. Therefore, it is desirable that the composition has an acidic pH. In one embodiment, when dissolved in water, the pH of the composition is between about 0 and about 6, particularly between about 1 and about 5, and particularly between about 2 and about 5.

[0028] Partly due to its low pH, the composition can effectively remove various debris and stains, such as hard water stains and scale. In practice, the composition must be contacted with a sufficient amount of water or a mixture of water and polar solvents to start the reaction required for cleaning the expected surface. Once the composition is exposed to water, the composition will begin to dissolve and foam. Water is used as a medium for reaction. Acid and gas generating agent react to release carbon dioxide, and carbon dioxide rises to the surface through an aqueous solution of a surfactant, produces bubbles in the solution and forms a foam layer on the surface. Foaming enables the composition to contact difficult-to-reach surfaces, such as the lower side of the inner surface of a flush toilet. In one embodiment, using 40g samples in 2 liters of water, after the sample tablet is immersed in the water for one to five minutes, a sufficient amount of foam is produced to have a foam height of at least about 0.1cm, at least about 0.5cm, at least about 0.75cm, at least about 1cm, at least about 1.25cm, at least about 1.5cm, at least about 1.75cm, at least about 2cm, at least about 3.0cm and at least about 3.5cm.

[0029] The composition has two key features: cleaning efficacy and the ability to be molded into various geometric shapes at room temperature. The cleaning efficacy includes effervescence, foaming, acidity and abrasive properties for removing hard water stains, scale and organic stains from the surface to be cleaned. In one embodiment, the composition can be added to water, wherein the cleaning efficacy is static without using mechanical force. In one embodiment, the composition can be used as a scrubber on the surface, wherein the cleaning efficacy is a convolution of static cleaning efficacy and washing by mechanical force. The additional features of the composition include fragrance, color, oxidation ability and antimicrobial properties, which can be incorporated into the basic formula of the composition to allow the production of a variety of cleaning products. In one embodiment, the composition can remove at least about 25%, at least about 50%, at least about 60%, at least about 70%, at least about 80%, at least about 90%, at least about 95% of hard water stains. In one embodiment, the solid composition can remove at least about 25%, at least about 50%, at least about 60%, at least about 70%, at least about 80%, at least about 90%, at least about 95% of scale.

[0030] After being molded into the concentrated solid form, the composition provides enough mechanical integrity, hardness, toughness and durability to be used on hard surfaces. In one embodiment, the solid composition is in the form of a tablet or pod that can be dripped into, for example, a flush toilet to provide cleaning. In one embodiment, the composition can be molded into a cleaning head and used in combination with a handheld tool. This provides a soluble head for use as a scrubbing tool, and provides the required chemical substance for cleaning. Therefore, the solid composition has the dual function of being used as a tablet and / or being used on the handle. The solid composition can also be first used on the handle to clean with mechanical force, and then released into water to carry out static cleaning.

[0031] The solid compressed composition must have a certain hardness and durability so that it will not dissolve or decompose immediately when it contacts water, and must keep the solid form long enough to contact and clean the surface. Tablet hardness is also described as tablet crushing force, which can be measured by most commercial instruments. The load when the tablet breaks along the diameter is recorded as tablet crushing force or hardness. Because the tablet size is relatively large, we modify the tensile testing machine for tablet hardness measurement. Tablet crushing force depends on the physical parameters of the tablet, including mass, geometric dimensions and shape. Including depressions in the tablet also affects crushing force. In one embodiment, when the solid compressed composition has a mass of 40 grams and a diameter of 48mm (± 1.0mm) and a height of 21.0mm (± 1.0mm) and a depression diameter of 29.8mm (± 1.0mm) and a depression height of 12.8mm (± 1.0mm) and is a rectangular shape with curved corners, the tablet crushing force is at least about 10lbf, about 15lbf, about 20lbf, and particularly at least about 25lbf. In one embodiment, the aged Shore A hardness of the solid compressed composition is at least about 30, specifically at least about 30, more specifically at least about 50 and about 100, even more specifically at least about 80. In one embodiment, the aged Shore D hardness of the solid compressed composition is between about 10 and about 100, specifically between about 20 and about 70. The amount of time that the composition remains in solid form can be measured as the dissolution time, which is defined as the time it takes for the 40 grams of solid compressed composition to disintegrate and dissolve when immersed in 2 liters of water without stirring after the 40 grams of solid compressed composition has been aged in air for two weeks under ambient conditions. The solid compressed composition has a dissolution time that is optimal for scrubbing the surface to be cleaned. In one embodiment, the dissolution time of the solid compressed composition is between about 1 minute and about 60 minutes, specifically between about 5 minutes and about 40 minutes, and specifically between about 10 minutes and about 30 minutes.

[0032] In order to prepare the solid composition of the present invention, the components are mixed together. If there is a fragrance, the fragrance is mixed with sodium carbonate. First, sodium carbonate and fragrance are mixed, then mixed with any surfactant to form a premix, and then the premix is ​​mixed with the mixture of the remaining components. The final mixture of the composition is added to a cavity or a mold, wherein, for example, a mechanical force is applied by a hydraulic press or a mechanical press to compress the mixture into a compressed product. The solid compressed product can adopt any geometric shape without departing from the expected scope of the present invention. After releasing from the cavity or the mold, the compressed product is aged in the air or in a sealed environment under ambient conditions to allow it to harden over time. In one embodiment, the solid composition obtained is pressed into tablets. In one embodiment, the solid composition is wrapped by a water-soluble polymer film to form a pod.

[0033] Example

[0034] Unless otherwise indicated or readily apparent from the context, all parts, percentages, ratios, etc. in the examples and the remainder of the specification are by weight.

[0035] Material

[0036] Table 1: Materials

[0037]

[0038] Test Method

[0039] Dissolution time

[0040] 2000 grams of water were added to a 4-liter beaker, followed by 40 grams of the sample tablet. Without stirring the solution, the tablet dissolution time was recorded when the tablet was completely dissolved.

[0041] pH Measurement

[0042] The pH of the dissolved solution was measured by a Thermo Fisher Scientific (Minneapolis, MN, United States) ORION STAR pH meter with an ORION ROSS pH electrode.

[0043] Tablet foam height measurement

[0044] 2000 grams of water were added to a 4-liter beaker, followed by 40 grams of the sample tablet. After two minutes, three minutes, and five minutes, the foam height of the effervescent tablet as it dissolved was measured and recorded.

[0045] Desktop drop test

[0046] The tablet is dropped from 0.5 m or 1 m above the tile surface with the bottom of the tablet facing the tile surface, and the impact strength of the tablet is rated as 1 if there are multiple fragments, 2 if there are several fragments, 3 if there are two fragments, 4 if there are cracks on the tablet, and 5 if the tablet is intact.

[0047] Tablet Strength Measurement

[0048] Tablet strength was measured using a Llyod LF Plus tensile tester by crushing the tablet in the diametrical direction (XY direction) and the calculated force (defined as the maximum load) used to crush the tablet was recorded in Newtons (N) and pounds-force (lbf).The tablet was secured by an internal fixture.

[0049] Contact angle measurement

[0050] The surface contact angle (CA) of the substrate was measured (in degrees) by a goniometer (NRL CA, model 100-00 115). A 1 microliter drop of deionized water was deposited on the surface of the tile substrate coated with the sample solution, and the contact angle was measured from the drop by illuminating it and recording the image with a camera. The image was analyzed computationally and the contact angle was calculated based on the tangent line.

[0051] Coating preparation and coating durability measurements

[0052] A 10.2 cm x 10.2 cm (4 inch x 4 inch) black tile substrate (obtained from Home Depot) was first cleaned with tap water and then air dried. The sample solution was prepared by mixing 980 grams of tap water in a 4-liter beaker, followed by the addition of 20 grams of sample over 10 minutes. The tile was then placed in the sample solution for a residence time of one minute or five minutes, rinsed with water to remove excess foam on the surface, and dried under ambient conditions. The contact angle was measured immediately, defined as the initial CA (0 minutes). The durability of the coating was measured by rinsing the coated tile under running water (flow rate of 168 grams / minute) for one minute, three minutes, five minutes, and ten minutes, and the contact angle was measured after it dried. All contact angle measurements are the average of three replicates.

[0053] Example 1 to Example 7 (EX1-EX7) and Comparative Example 1 to Comparative Example 2 (CE1-CE2)

[0054] The amounts (weight percent) of the materials identified in Table 2 were combined and mixed with an Eirich intensive mixer for two to twenty minutes.

[0055] Tablets with a diameter of 48 mm and a weight of 40 g were prepared on a hydraulic press (MTV4-SD-120T-S, MULTITECH, Hong Kong) at a compression speed of 0.1 m / s and a residence time of 1 s. The approximate force for tableting was about 95 kg / cm 2 .

[0056] Table 2: Tablet composition (weight percentage)

[0057]

[0058] The tests were performed and the results are presented in Table 3.

[0059] Table 3: Tablet sample test results

[0060]

[0061]

[0062] Example 8 to Example 17 (EX8 to EX17)

[0063] The amounts (weight percent) of the materials identified in Table 4 were combined and mixed with an Eirich intensive mixer for two to twenty minutes.

[0064] Tablets with a diameter of 48 mm and a weight of 40 g were prepared on a hydraulic press (MTV4-SD-120T-S, MULTITECH, Hong Kong) at a compression speed of 0.1 m / s and a residence time of 1 s. The approximate force for tableting was about 95 kg / cm 2 .

[0065] Table 4: Tablet composition (weight percentage)

[0066] EX8 EX9 EX10 EX11 EX12 EX13 EX14 EX15 EX16 EX17 PEG-1 0.3 0.3 0.3 0.3 0.3 0.3 0.0 0.0 0 0 Blue Dye 0.01 0.01 0.01 0.01 0.01 0.01 0.0 0.0 0.02 0.02 Sodium metabisulfite 0.06 0.06 0.06 0.06 0.06 0.06 0.0 0.0 0 0 <![CDATA[ Na 2 CO 3]]> 23.0 23.0 23.0 23.0 23.0 23.0 23.1 23.3 23 23 lemon 0.3 0.3 0.3 0.3 0.3 0.3 0.0 0.0 0 0 Citrus 0.0 0.0 0.0 0.0 0.0 0.0 0.3 0.32 0.3 0.3 Polyacrylic acid-1 1.5 1.5 1.5 1.5 1.5 1.5 3.0 0.0 0 0 Polyacrylic acid-2 0.0 0.0 0.0 0.0 0.0 0.0 0.0 3.0 0 5 Sodium salt 1.5 1.5 1.5 1.5 1.5 1.5 1.5 1.5 1.5 1.5 LAL 2.5 2.5 2.5 2.5 2.5 2.5 2.5 2.64 2.5 2.5 Silicate 0.5 0.5 0.5 0.5 0.5 0.5 0.48 0.5 0.5 0.5 Plaster of Paris 10.0 5.0 9.7 5.0 5.0 5.0 5.0 4.96 5 5 Citric Acid 10.3 11.5 10 20 30 48 11.0 11.1 31.1 28.6 Sulfamic acid 50 48.8 45.6 40.3 30.3 12.3 47.7 47.7 31.1 28.6 PEG-2 0.0 5.0 5.0 5.0 5.0 5.0 5.0 5.1 5 5 pH 2.0 2.2 2.5 2.7 3.4 4.2 2.8 2.5 3.7 3.7

[0067] Examples 8 to 13 were tested and the results are presented in Table 5.

[0068] Table 5: Tablet sample test results

[0069]

[0070] Tests for “Contact angle measurement” and “Coating durability measurement” were performed on Examples 14 to 17, and the results thereof are presented in Table 6.

[0071] Table 6: Tablet sample test results

[0072]

[0073] The above antimicrobial testing was performed on Example 1 and Example 16, and the results are presented in Table 7.

[0074] Table 7: Log Reduction in Antimicrobial Killing

[0075]

[0076] Although the present invention has been described with reference to preferred embodiments, workers skilled in the art will recognize that changes may be made in form and detail without departing from the spirit and scope of the invention.

Claims

1. A cleaning product, comprising: Inorganic binder; Gas generating agent; a strong acid having a pKa between about -3 and about 2; a weak acid having a pKa between about 2.5 and about 5, wherein the ratio of the strong acid to the weak acid is between about 50:1 and about 1:50; and at least about 0.1% water, Wherein when the cleaning article has a diameter of about 48 mm and a height of about 21 mm and a recessed diameter of about 29.8 mm, a recessed height of about 12.8 mm, and a mass of about 40 grams, the cleaning article has a tablet breaking force of at least about 10 lbf and a dissolution time of between about 1 minute and about 60 minutes.

2. The cleaning article according to claim 1, further comprising an organic binder.

3. The cleaning product according to claim 1, further comprising one of a chelating agent, a surfactant, a hydrophilic agent, a lubricant, a release agent, an oxidant, an antimicrobial agent, a biocide, a fragrance, and an anti-caking agent.

4. The cleaning article of claim 2, wherein the organic binder is polyethylene glycol.

5. The cleaning article of claim 2, wherein the organic binder is polyethylene glycol having an average molecular weight ranging between about 400 g / mol and about 500,000 g / mol.

6. The cleaning article according to claim 1, wherein the strong acid is selected from one of alkyl sulfonic acid, aryl sulfonic acid and oxalic acid.

7. The cleaning article of claim 1 wherein the weak acid is a carboxylic acid.

8. The cleaning article of claim 1 wherein the strong acid and the weak acid are organic acids.

9. The cleaning article of claim 1, wherein the cleaning article has a break force of at least about 25 lbf.

10. The cleaning article of claim 1, wherein the cleaning article has cleaning efficiency when used with or without mechanical forces.

11. A solid cleaning composition, comprising: an inorganic binder that reacts with water and hardens to form a hardened structure; Gas generating agent; a strong acid having a pKa between about -3 and about 2; and a weak acid having a pKa between about 2.5 and about 5, wherein the strong acid and the weak acid are present in a ratio between about 50:1 and about 1:50; and Waterborne polymer.

12. The solid cleaning composition according to claim 11, further comprising an organic binder.

13. The solid cleaning composition according to claim 12, wherein the organic binder is one of a sugar and an organic acid salt.

14. The solid cleaning composition according to claim 11, wherein the organic binder is polyethylene glycol.

15. The solid cleaning composition of claim 11, wherein the solid cleaning composition has a pH of between about 0 and about 6 when dissolved in water.

16. The solid cleaning composition of claim 11, wherein the strong acid and the weak acid are organic acids.

17. The solid cleaning composition of claim 11, wherein the ratio of the strong acid to the weak acid is between about 11:1 and about 1:

11.

18. The solid cleaning composition of claim 11, wherein the cleaning article has a break force of at least about 10 lbf.

19. The solid cleaning composition of claim 11, wherein the cleaning article has an aged Shore A hardness of at least about 10 and an aged Shore D hardness of at most about 100.

20. The solid cleaning composition of claim 11, wherein the cleaning article has cleaning efficiency when used with or without mechanical forces.